Forty studies that changed psychology explorations into the history of psychological research - Hock, Roger R. 1948- (Pearson Education Limited, 2015)
Summary "This unique book closes the gap between psychology textbooks and the research that made them possible by offering a first hand glimpse into 40 of the most famous studies in the history of the field, and subsequent studies that expanded upon each study's influence. Readers are able to grasp the process and excitement of scientific discovery as they experience an insider's look at the studies that continue today to be cited most frequently, stirred up the most controversy when they were first published, sparked the most subsequent related research, opened new fields of psychological exploration, and changed most dramatically our knowledge of human behavior." --Publisher's description.